Review: Christianity in the Making, volume 1: Jesus Remembered - Bockmuehl, M. (The journal of theological studies, 2005)
Christianity in the Making, volume 1: Jesus Remembered James D. G. Dunn xviii + 1019 Grand Rapids, MI William B. Eerdmans 2003 0 8028 3931 2 £39.95/$55